Peran Guru Pendidikan Jasmani Sekolah Dasar dalam Meningkatkan Pelaksanaan Usaha Kesehatan Sekolah di SD Negeri Se-Desa Kayen Kabupaten Pati - santi, susanti; Irsyada, Roas (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine the role of elementary school physical education teachers in improving the implementation of UKS in public elementary schools throughout Kayen Village. The method used is descriptive quantitative with a population of 6 Public Elementary Schools in Kayen Village and the sample used by all physical education teachers in State Elementary Schools in Kayen Village is 6 teachers (total sampling). The test instrument uses a questionnaire and documentation. The analysis technique uses the percentage score formula and the descriptive percentage analysis criteria table from Sudijono in 2009. The results show that the role of physical education teachers in improving the UKS of Public Elementary Schools throughout Kayen Village, Pati Regency is carried out well along with several factors such as: instilling healthy living habits (67%) , teaches students hygiene (83%), supervises and checks the cleanliness of the school environment (50%), performs first aid and light treatment (67%), recognizes signs of infectious diseases and their consequences (67%), knows efforts as an action next (83%). The role of physical education teachers in UKS activities at State Elementary Schools throughout Kayen Village has been going well, because they have taken 6 factors to support the implementation of UKS.